FRI0337 anti-C1Q Autoantibodies, C1Q Circulating Immune Complexes and Complement Levels in Patients with Neuropsychiatric Systemic Lupus Erythematosus. (15th July 2016) - Magro-Checa, C.; Schaarenburg, R.A.; Beaart, H.J.L.; Huizinga, T.W.; Steup-Beekman, G.M.; Trouw, L.A.
Abstract : Background: Experimental SLE-models show that complement activation may be a key part of lupus cerebritis and lupus-thrombosis. It is also known that complement factors contribute to the pathology of inflammatory central nervous system (CNS) and neurodegenerative diseases Objectives: To analyse serum levels of anti-C1q, C1q circulating immune complexes (CIC), complement activation and complement components in systemic lupus erythematosus (SLE) patients during the first CNS neuropsychiatric (NP) event and to define the possible association between these results and clinical and laboratory characteristics Methods: Patients suspected of having NP involvement due to SLE were recruited in the Leiden NPSLE-clinic. All SLE patients were classified according to the ACR 1982 revised criteria for the classification of SLE. The clinical disease activity was measured by the SLE Disease Activity Index 2000 (SLEDAI-2K) and NP diagnoses were classified according to the 1999 ACR case definitions for NPSLE. We measured in serum of all patients anti-C1q and C1q CIC levels using ELISA, the activation capacity of complement (CH50 and AP50) using functional assays and different complement components (C1q, C3, C4) using laser nephelometry. Two-hundred healthy controls (HC) were also included for comparison Results: A total of 280 patients were included. In 92 patients the symptoms were attributed to SLE. NPSLE patients consisted of 63 patients with focal NPSLE and 34 patients with diffuse NPSLE. Anti-C1q antibodies were significantly higher and CH50, AP50 and C3 were significantly lower in NPSLE patients compared to SLE and HC. This association was specially marked for diffuse NPSLE (SLE: 20.8 versus 8.7; HC: 20, 8 versus 7, 04; both comparisons P <0.05). No differences in antibody titters were found for C1q CIC when SLE and NPSLE patients where compared. Low C4 was significantly associated with focal NPSLE after using potential predictors, but we lost this association when antiphospholipid antibodies (aPL) were excluded from the model. Low C3, AP50 and CH50 were independently associated with diffuse NPSLE ( P <0.001). When SLEDAI-2K was included in the model we did not find any association. When individual NPSLE syndromes were analysed, psychosis and cognitive dysfunction showed significantly lower values of AP50 and CH50 ( P <0.001 for psychosis and P <0.05 or cognitive dysfunction). Furthermore, patients with lupus psychosis showed higher prevalence of low C1q (OR=5, 95% CI 1.5–15.8, P <0.05), low C3 (OR=28.6, 95% CI 3.5–230.4, P <0.001) and low C4 (OR=3.8, 95% CI 1.1–13.3, P <0.05) and cognitive dysfunction showed a higher prevalence of low C1q (OR=5, 95% CI 1.5–15.8, P <0.05), low C3 (OR=4.4, 95% CI 1.8–10.5, P <0.001) and low C4 (OR=3.6, 95% CI 1.5–8.6, P <0.05) when compared with SLE. No significant associations were seen with other individual NPSLE syndromes Conclusions: No association was found between anti-C1q, C1q CIC and NPSLE. The associations between diffuse NPSLE and low C3/AP50 and focal NPSLE and low C4 may be explained by disease activity and the presence of aPL respectively. The role of complement activation and complement components in lupus psychosis and cognitive dysfunction merits further research References: Jacob A et al. C3aR inhibition reduces neurodegeneration in experimental lupus. Lupus 2010;19:73–82 Disclosure of Interest: None declared